Drivers, timing and some impacts of global aridity change. (5th October 2018) - Lickley, Megan; Solomon, Susan
Abstract: The modeled robustness of the aridity response to climate change has already been well established: global drylands are expanding as increases in potential evapotranspiration outpace precipitation increases. This work considers three questions not previously addressed: (1) in which aridity zones are aridity trends expected to first emerge? (2) To what extent are future populations expected to experience changes in aridity? (3) For which locations and populations is aridity change determined by changes in precipitation versus temperature? Using a multi-model ensemble of general circulation models (GCMs) from the CMIP5 archives, together with population statistics from United Nations databases we find the following: (1) drier regions are projected to dry earlier, more severely and to a greater extent than humid regions. (2) By the end of the century, up to 700 million more people are projected to live in arid regions, with half of humankind living in regions experiencing drying of at least 5% and 3 billion experiencing 25% drying under a high emissions scenario. The largest populations to experience extreme drying are in Africa and Asia. According to GCMs, aridity increases have already begun to emerge in Northern Africa. Populations in sub-Saharan Africa appear to be the most vulnerable considering current water scarcity levels there. And (3) precipitation change is projected to drive the most severe drying in arid regions, contributing to the earliest emerging signals of aridity change and driving the differential drying across aridity zones. A comparison of aridity data derived from observations with model ensemble data suggests that increased aridity is already emerging in the driest regions. In sum, widespread aridity trends across a warming state imply that most of humanity will live in a more arid world.